2006
DOI: 10.1080/15622970500213871
|View full text |Cite
|
Sign up to set email alerts
|

The influence of concomitant antidepressant medication on safety, tolerability and clinical effectiveness of electroconvulsive therapy

Abstract: Our study supports the hypothesis that mirtazapine can be used to enhance the therapeutic effectiveness of ECT. Controlled studies are necessary to further investigate the possible advantages of ECT and pharmacotherapy combinations, especially the use of modern dually acting antidepressants which have proven their good effectiveness in treatment-resistant depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 33 publications
0
27
1
1
Order By: Relevance
“…In this respect, it has to be noted that the present results were not corrected for potentially confounding influences of further polymorphisms within the dopaminergic system previously found to be associated with ECT response, such as COMT Val 158 Met or DRD2 C957T Domschke et al 2009 ;Huuhka et al 2008), BDNF gene variation (Fernandes et al 2009 ;Huuhka et al 2007) or polymorphisms impacting ventral striatum responsiveness to emotional stimuli such as DAT 40-bp 3kVNTR or CNR1 rs1049353 (Chakrabarti et al 2006 ;Domschke et al 2008 ;Hahn et al 2011). Additionally, since 71.2 % of the present investigated patients concomitantly received antidepressant pharmacotherapy, 79.8 % adjunct neuroleptic medication and 20.2 % anxiolytic agents as invariably done in daily clinical practice, the present effect -although not statistically significant in our sample -could be influenced by concomitant antidepressant (Baghai et al 2006), antipsychotic -9 -7 -5 -3 -1 -9 -7 -5 -3 -1 (a) (b) Fig. 2.…”
Section: Discussionmentioning
confidence: 50%
“…In this respect, it has to be noted that the present results were not corrected for potentially confounding influences of further polymorphisms within the dopaminergic system previously found to be associated with ECT response, such as COMT Val 158 Met or DRD2 C957T Domschke et al 2009 ;Huuhka et al 2008), BDNF gene variation (Fernandes et al 2009 ;Huuhka et al 2007) or polymorphisms impacting ventral striatum responsiveness to emotional stimuli such as DAT 40-bp 3kVNTR or CNR1 rs1049353 (Chakrabarti et al 2006 ;Domschke et al 2008 ;Hahn et al 2011). Additionally, since 71.2 % of the present investigated patients concomitantly received antidepressant pharmacotherapy, 79.8 % adjunct neuroleptic medication and 20.2 % anxiolytic agents as invariably done in daily clinical practice, the present effect -although not statistically significant in our sample -could be influenced by concomitant antidepressant (Baghai et al 2006), antipsychotic -9 -7 -5 -3 -1 -9 -7 -5 -3 -1 (a) (b) Fig. 2.…”
Section: Discussionmentioning
confidence: 50%
“…Also, the present study does not allow for evaluation of a molecular pattern with a set of variations in a set of molecularly correlated enzymes related to COMT. Additionally, since 71.2% of the patients concomitantly received antidepressant pharmacotherapy as invariably done in daily clinical practice, the present effect-although not statistically significant in our sample-could be influenced by concomitant antidepressant pharmacotherapy [Baghai et al, 2006] and might therefore not be specific for ECT. Furthermore, the relatively small sample sizes of patients in the diagnostic subgroups (HAM-D sub-factors, gender) might have increased the risk for a false-negative or false-positive result.…”
Section: Cogenetics; Gendermentioning
confidence: 61%
“…In general bilateral ECT is considered to be more effective than unilateral ECT and high-dosage ECT has been suggested to be more effective than low-dosage ECT (ECT Review Group 2003). Furthermore, several investigations suggested that concomitant psychopharmacological treatment administered during the course of ECT may alter the efficacy and safety of ECT (Baghai et al 2006;Nothdurfter et al 2006). In a first retrospective investigation we found that concomitant administration of mirtazapine and atypical antipsychotics enhanced the therapeutic effectiveness of ECT.…”
Section: Introductionmentioning
confidence: 83%